Sediment supply control on the delivery of sediments to deep‐lacustrine environment: A case study from Luanping Basin, northern China. (19th August 2019) - Jia, Haibo; Ji, Hancheng; Yu, Jifeng; Meng, Xiangchao
Abstract : Deep‐water deposits in marine basins have recently received considerable research attention. However, the controls of sediment transported to deep‐lacustrine environments are comparatively understudied. In this study, we utilize field‐based outcrop data to investigate the variability of sediment distribution and its controlling factors in the Lower Cretaceous synrift Xiguayuan Formation in the Luanping Basin. Two fan‐delta systems with variability dominate the measured outcrop sections. At the lithological scale, the ratio of conglomerate to strata in the Xiyuan fan‐delta system is 87%, and the average thickness of individual coarse‐grained layers is ~1 m; the corresponding values in the Caoying fan‐delta system are 52% and 0.4 m. In addition, sand‐rich gravity‐flow deposits are developed in front of the Xiyuan fan delta, whereas mud‐rich mass transport deposits (i.e., sliding block and slumping debris) are found in front of the Caoying fan delta. At the stratigraphical scale, a delta succession in the Xiyuan section characterized by sand‐rich facies from proximal to distal parts is developed in a relatively steep slope setting. In the Caoying section, however, a delta succession characterized by sand‐rich facies in the proximal to middle parts is found in addition to a mud‐rich distal part developed in a gentle slope setting. Differential sediment supply resulted in significant variation in the sediment distribution pattern. In particular, the grain size of the fan‐delta front controls that of the deep‐lacustrine gravity‐flow deposits fed by them. This study highlights the variability of sediment supply and their control on sediment partitioning in continental rift and marine basins.